Upper Limb Function and Cortical Organization in Youth with Unilateral Cerebral Palsy - Mackey, Anna; Stinear, Cathy; Stott, Susan; Byblow, Winston D. (Frontiers in Neurology, 2014)
Aim: To explore the relationship between motor cortical and descending motor pathway reorganization, lesion type, and upper limb function in youth with unilateral cerebral palsy (CP). Methods: Twenty participants with unilateral CP (mean age 15 ± 3 years; 11 males) completed a range of upper limb functional measures. Structural MRI, diffusion-weighted, and functional MRI were conducted to determine type and extent of brain lesion, descending white matter integrity, and whole-brain activity during affected hand use. Single pulse transcranial magnetic stimulation (TMS) (n = 12) was used to examine functional integrity of the corticospinal pathway as well as primary motor cortex intracortical and interhemispheric inhibition from motor-evoked potentials and silent periods. Results: Fractional anisotropy measures within the posterior limb of the internal capsule were a predictor of upper limb function (R2 = 0.41, F = 11.3, p = 0.004). Participants with periventricular lesions tended to have better upper limb function [F(2, 17) = 42.48, p < 0.0001]. Five participants with evidence of cortical reorganization and functional ipsilateral projections to their affected hand had worse upper limb function. Deficits in intracortical and interhemispheric inhibitory mechanisms were found in participants with worse upper limb function (Melbourne Assessment of Unilateral Upper Limb Function: Mann Whitney p = 0.02). Conclusion: Neuroimaging and TMS can provide useful information related to hand function of individuals with unilateral CP and may have potential to assist as a predictive tool and/or guide rehabilitation.